1995
DOI: 10.1007/bf02148842
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of benign anal disease with topical nitroglycerin

Abstract: Topically applied nitroglycerin ointment appears to have a therapeutic role in the treatment of thrombosed external hemorrhoids and anal fissure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(46 citation statements)
references
References 17 publications
1
42
0
3
Order By: Relevance
“…In 1997, following the publication of successful pilot studies [105][106][107], a randomised prospective, double-blind clinical trial was reported that compared topical 0.2% GTN ointment to placebo in chronic anal fissure. At 8 weeks, two-thirds of patients in the GTN arm had successful healing of their anal fissures compared with only 8% of those applying a placebo [108].…”
Section: Nitratesmentioning
confidence: 99%
“…In 1997, following the publication of successful pilot studies [105][106][107], a randomised prospective, double-blind clinical trial was reported that compared topical 0.2% GTN ointment to placebo in chronic anal fissure. At 8 weeks, two-thirds of patients in the GTN arm had successful healing of their anal fissures compared with only 8% of those applying a placebo [108].…”
Section: Nitratesmentioning
confidence: 99%
“…Recently, its value in wound healing and as an antimicrobial agent has been appreciated (9,16). From a safety standpoint, the worst-case systemic exposure occurs if a lock is inadvertently flushed, in which case a bolus dose is presented.…”
Section: Discussionmentioning
confidence: 99%
“…Referências da literatura têm demonstrado que pacientes portadores de doença hemorroidária, assim como de fissura anal, apresentam pressões anais aumentadas, à custa de hipertonia do esfíncter anal interno 5,6,14 . No entanto, ainda não está bem definido se o aumento da pressão anal é secundário à presença dos coxins vasculares 30,31 , e se interfere no retorno venoso do plexo hemorroidário interno, causando degeneração das estruturas fibromusculares e deslizamento progressivo dos coxins anais 32,33 .…”
Section: Manometriaunclassified
“…Vários estudos de eletromanometria anorretal demonstraram que, pacientes portadores de doença hemorroidária, podem apresentar pressão do canal anal aumentada, semelhantemente ao que ocorre na fissura anal 4,5,7,8 . Existem vários relatos na literatura que mostram que a hipertonia do esfíncter interno do ânus exerce um papel etiológico, tanto no desenvolvimento da fissura anal, como na doença hemorroidária 6,9 . Alguns autores sugerem que a esfincterotomia lateral interna associada à hemorroidectomia, pode contribuir para uma melhor evolução clínica no pós-operatório (redução da dor, da retenção urinária, da estenose anal e do tempo de cicatrização da ferida operatória) 4,[10][11][12][13] .…”
Section: Introducãounclassified